ANALISA GAMBARAN POST MORTEM MAKROSKOPIS DAN MIKROSKOPIS ORGAN PARU DAN USUS HALUS PADA TIKUS WISTAR SETELAH PEMBERIAN WARFARIN LD-50 DAN LD-100 - Mada Aji Prakoso; Gatot Suharto; Siti Amarwati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Introduction : More than 800.000 people died every years from suicide, and in 2012 suicidal acts on 15-29 years old become the second most cause. Suicide by poison is one of the most used, Warfarins role here aside from its therapeutical effect as anticoagulant, and also as rodenticide in household often misused for a way to suicide. This study is aimed to analyze the differences of macroscopic and microscopics representation in lungs and small intestine on Wistar mouse after LD50 dan LD100 Warfarin administration.Method : This is experimental analytic study, using total sample of 27 mouse, male Rattus norvegicus as the sample. These 27 mouse will be divided into 3 group, 9 eachs. First group is administered LD50 Warfarin, second group is administered LD100 Warfarin, and the third group as control.Result : there is no differences in macroscopic aspect of lung control group with group LD50 dan LD100, in microscopic showed massive haemmorhage. On small intestines there is differences from control group with LD50 dan LD100.Conclussion : Toxic effect from warfarin showed in microscopic view of organs with hemorrhage and destruction of its tissues.